ERP Transformation in Life Sciences: Strategic and Architectural Challenges - Sudhakar Reddipalli (Journal of Computational Analysis and Applications (JoCAAA), 2026)
Enterprise resource planning transformation in pharmaceutical organizations presents unique challengesthat require comprehensive strategic planning, sophisticated technical architecture, and rigorouscompliance management. This article examines the complex interplay between regulatory requirements, global operational coordination, and technology modernization